Management of secondary nutrients and micronutrients in rice under ricewheat cropping system in acid soil - Saha, P B; Jha, A K; Aind, W; Chaterjee, K (ORYZA-An International Journal of Rice, 2020)
A field experiment was conducted in the experimental farm of Zonal Agricultural Research Station, Dumka, Birsa Agricultural University, Ranchi, Jharkhand during kharif seasons of 2015, 2016 and 2017 to study the effects of secondary and micronutrients on rice under rice-wheat cropping system in acid soil. The experimental findings have been interpreted in terms of grain yield, crop response (%), P, K, S and B -uptake by the crop. There were seven treatment combinations viz., NPK (RD) [@ (80 : 40 : 20) kg / ha], NPK + FYM [@ 3t / ha],NPK + lime [@ 4q / ha], NPK + S [@ 30kg / ha], NPK + S + B [@ 200 ppm foliar spray as borax], NPK + S + B + Si [@ 20 kg K - silicate / ha] and (NPK + FYM + S + B + Si). The experiment was laid out in RBD with three replications. It was found that the highest grain yield (40.60 q / ha) was obtained with the combined application of (NPK + FYM + S + B + Si), which also corresponded to the maximum crop response (24.4%). It was also found that application of micronutrients alone did not have significant effects on S and B-uptakes unless they were applied in combination with FYM. The highest S-uptake (7.40 kg/ha) and B-uptake (126.03 g/ha) were recorded with (NPK + FYM + S + B + Si). The highest P-uptake (13.74 kg/ha) and K-uptake (16.11 kg/ha) were obtained with (NPK + Lime).